New Stabilizers for Poly(vinyl chloride) Derived from 1,1 -Bis (4-aminophenyl) -4-Phenyl Cyclohexane Compounds[II] - Salman, Hussein N; Nief, Olfat A; Ahmed, Ahmed A (Al-Nahrain Journal of Science, 2018)
This article included the photostabilization study for poly(vinyl chloride)) by using newly stabilizers derived from [1,1 -Bis (4-aminophenyl)-4-Phenyl Cyclohexane] as additives against photodegradation. For that purpose, many samples (films) has been prepared by adding additives to the poly(vinyl chloride) with different weight percentages from additives and by different thickness. The photostabilization activities of these compounds were determined by detecting the carbonyl group (The position off carbonyl absorption is specified at 1724-1770 cm-1) with irradiation time. The absorption spectra of poly vinyl chloride films were followed using Shimadzu Spectrophotometer Also, change the viscosity of the averagee molecular weight and the degree of deterioration (α) and the average number of chain scission (s) was studied .We found through results that the rate of photostabilization in the presences of additives follows the following trend:- C4 > C3 > C2 > C1 > PVCUV absorption peroxide decomposer, for mechanisms haven been suggested according to experimental results obtained.